Vacuum-assisted laparostomy with staged peritoneal lavage in management of secondary postoperative diffuse peritonitis: a prospective comparative non-randomised clinical trial - I. B. Uvarov; D. D. Sichinava; A. M. Manuilov (Кубанский научный медицинский вестник, 2022)
Background. Secondary postoperative diffuse peritonitis (SPDP) associates with a high incidence of abdominal sepsis and 35–92% mortality rate. An optimal surgical doctrine in this complication in lacking to date.Objectives. An efﬁcacy assessment of vacuum-assisted laparostomy (VAL) with staged lavage relative to relaparotomy on demand (RD) in SPDP patients.Methods. Patient enrolment and analyses were conducted within period 01.11.2017-31.12.2020, totalling for 141 SPDP patients, 77 (54.6%) males and 64 (45.4%) females aged 64.5 (5972.7) years. Cohort I patients (n = 52) had post-abdominal-lavage VAL using Suprasorb® SNP (SNP-1 and SNP-2) equipment and consumables (Lohmann & Rauscher GmbH, Austria). Staged lavage was performed 48-72 h apart. Cohort II (n = 78) had a standard RD  technique. Cohort III (n = 11) treatment included RD-to-VAL transition. The endpoint was the inpatient treatment outcome, a favourable completion or death. The additional estimated criteria were complications rate and severity (in ACCORDION-modiﬁed Clavien-Dindo classiﬁcation), sepsis rate, C-reactive protein level, abdominal index dynamics, patient’s intensive-care and total-hospital lengths of stay.Results. Cohort I included 157 staged-lavage VALs, cohort II — 107 RDs, cohort III — 49 operations. The mortality rate was 3/52 (5.8%), 24/78 (30.8%) and 7/11 (63.6%) in cohorts I, II and III (respectively, p < 0.001). No difference was observed in the length of hospital stay, with a shorter intensive care stay after ﬁnal abdominal closure in cohort I. Clavien — Dindo grade 3a complications were observed for 25.0% of cohort I, 60.3 and 45.5% — of cohorts II and III (respectively, p < 0.01); grade 3b complications were 0 (0%), 24.4 and 100% in cohorts I, II and III (respectively, p < 0.001; all 11 patients were reoperated). Multiple organ failure (grade 4b) was reported in 5.8, 30.8 and 63.6% of cohorts I, II and III (respectively, p < 0.001). By end of treatment, sepsis had resolved in 9/11 (81.8%) patients in cohort I, 5/24 (20.8%) and 1/6 (16.7%) — in cohorts II and III (respectively, p = 0.002).Conclusion. Programmed staged-lavage VAL is an optimal surgical treatment tactics in SPDP. Relative to RD, VAL provides a more effective management of local and systemic abdominal sepsis, lower mortality, fewer and less sever complications, shorter intensive care stays after abdominal closure.